PEMBUATAN SISTEM DATA LAYANAN POSYANDU BALITA DI DESA MALI COT KECAMATAN SAKTI KABUPATEN PIDIE - Khairul Fuady (Universitas Negeri Medan, 2023)
The Health of the children is important during the process of the growth and will to the creation of a healthy generation in the future. Problems related to the children in Indonesia such as malnutrition, underweight, stunting, and lack of immunization must be the common concern. The impact is that it disrupts brain development, intelligence, physical growth disorders, and metabolic disorders in the body which results in decreased cognitive ability and learning achievement, decreased immunity so that you get sick easily, and a high risk of developing degenerative diseases in adulthood. Posyandu is a form of community-based health efforts (UKBM) managed and organized by the community in implementing health development, in order to empower the community and provide convenience to the community in obtaining basic health services. Posyandu activities can be carried out using information technology. The creation of a toddler posyandu service data system is an alternative to mapping various problems related to the children in a village/gampong and presenting valid data that can be monitored in real time and from time to time. The creation of the Posyandu Service Data System (SDLP) in Mali Cot Village, Sakti District, Pidie Regency is expected to become a pilot project to be developed in the future.